The effects of different classroom lighting on sleep quality in adolescents - Auður Pálsdóttir 1995-; Kristín Erna Sigurjónsdóttir Waage 1993- (2023)
Quality sleep is essential during the formative adolescent years, but poor sleep quality is still a prevailing problem for many adolescents. Light therapy has shown promising results in improving sleep quality and this study examined if an intervention, with two different lighting conditions in classrooms, affected sleep quality among first year, healthy upper-secondary school students in Iceland. It was hypothesised that the intervention would improve global sleep quality of students or some of the seven components of sleep quality. Two different lighting conditions were installed in the classrooms where students attended most of their classes. Participants (N = 31) completed a questionnaire regarding sleep quality at four different timepoints during the intervention, from October to April. The results showed that the different lighting conditions did not have a significant effect on participants’ sleep quality. However, out of seven components of the sleep quality scale, the intervention did significantly affect two; sleep latency increased, and daytime dysfunction decreased. However, these are preliminary results which need to be viewed with caution and further analysis will be undertaken. Further studies, utilising simple and non-invasive ways to improve sleep quality of adolescent, are needed on this topic. Keywords: sleep quality, adolescents, light therapy, intervention Gæðasvefn er mikilvægur á mótandi tíma unglingsáranna en léleg svefngæði hrjá þó marga unglinga. Ljósameðferð hefur lofað góðu sem aðferð til að bæta svefngæði og í þessari rannsókn var skoðað hvort íhlutun, með tveimur mismunandi lýsingum, hefði áhrif á svefngæði á meðal heilbrigðra ungmenna á fyrsta ári í framhaldsskóla á Íslandi. Tilgátur voru settar fram og gerðu þær ráð fyrir að íhlutunin myndi bæta heildar svefngæði nemenda eða bæta einhverja af sjö undirþáttum svefngæða. Tvær tegundir af lýsingu voru settar upp í þeim skólastofum sem nemendur vörðu hvað mestum tíma í. Þátttakendur (N = 31) svöruðu spurningalista varðandi svefngæði ...